A taxonomic revision of Pollia (Commelinaceae) in India with six lectotypifications - Jameera, A.; Nampy, Santhosh; Janeesha, A.p. (Phytotaxa, 2016)
The genus Pollia consisting of five species in India is revised based on field and herbarium studies. Detailed descriptions, illustrations, photoplates and key to the identification of Indian species are provided. Six names viz., Aclisia indica, Pollia pentasperma, P. secundiflora, P. subumbellata, P. thyrsiflora and P. aclisia var. robusta are lectotypified.